Early intestinal perforation secondary to congenital mesenteric defects - Ingrid Anne Mandy Schierz; Mario Giuffrè; Mariaserena Lo Presti; Giuseppa Pinello; Cinzia Chiaramonte; Enrica Maria Agosta Cecala; Giovanni Corsello (Elsevier, 2016)
Gastrointestinal perforation (GIP) in preterm neonates may be idiopathic, due to necrotizing enterocolitis (NEC), or mechanical obstruction. The predominant cause of GIP in the neonatal period is NEC. Differential diagnosis with congenital malformations, including mesenteric defects leading to internal hernias, is mandatory if the onset is early. We describe two newborns with trans-mesenteric herniation resulting in GIP, and we discuss the presence of possible additional risk factors such as prematurity and predisposing vascular disruption in connective tissue disorders (Ehlers-Danlos syndrome), twinning, and use of assisted reproductive technologies. These cases prompted us to review our exploratory laparotomies performed for intestinal obstruction, complicated/or not with perforation, to identify the frequency of neonatal trans-mesenteric hernias in a referral hospital. The prevalence of GIP and of internal hernia was 25% and 3.3%, respectively. In conclusion, time-onset and particular conditions associated with GIP should lead to a high index of suspicion for internal hernias in order to achieve appropriate diagnosis and therapy.